2018
DOI: 10.1371/journal.pgen.1007275
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of glycemic trait loci in the China Health and Nutrition Survey

Abstract: To identify genetic contributions to type 2 diabetes (T2D) and related glycemic traits (fasting glucose, fasting insulin, and HbA1c), we conducted genome-wide association analyses (GWAS) in up to 7,178 Chinese subjects from nine provinces in the China Health and Nutrition Survey (CHNS). We examined patterns of population structure within CHNS and found that allele frequencies differed across provinces, consistent with genetic drift and population substructure. We further validated 32 previously described T2D- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 83 publications
5
22
0
Order By: Relevance
“…Furthermore, more than 200 SNPs were found to reach the level of a suggestive association. We compared our results with previously reported SNPs [ 25 27 , 37 40 ] and found that 8 SNPs could be replicated, indicating our results were credible.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, more than 200 SNPs were found to reach the level of a suggestive association. We compared our results with previously reported SNPs [ 25 27 , 37 40 ] and found that 8 SNPs could be replicated, indicating our results were credible.…”
Section: Discussionsupporting
confidence: 57%
“…Within the East Asian meta-analysis, the direction of effect is consistent across East Asian countries ( Extended Data Figure 9B ) and within the contributing cohorts ( Extended Data Figure 9C ). The T2D risk allele rs12712928-C is associated with higher fasting glucose levels in East Asian populations, has the strongest association with lower expression levels of both SIX3 and SIX2 in pancreatic islets 19 , and demonstrated allele-specific binding to the transcription factor GABPA and significantly lower levels of transcriptional activity 36 . While rs12712928-C is present on only one common haplotype in most populations, it is present on an additional common haplotype (frequency =0.075) in East Asians, suggesting that the effect size attributed to rs12712928 may be influenced by other nearby unknown variants.…”
Section: Resultsmentioning
confidence: 99%
“…As such, understanding the genetic predisposition to particular phenotype measurements, and the factors that confound them, has implications for disease treatment. While the genetics of some biomarkers have been extensively studied, most notably lipids 1 , 2,3 , glycaemic traits [4][5][6] , and measurements of kidney function [7][8][9] , most biomarkers have only had limited measured genetic contribution.…”
Section: Introductionmentioning
confidence: 99%